Germination Viability of Maize M1 Seeds (Zea mays L.) after Gamma Ray Irradiation - Rafiuddin Rafiuddin; Dahliana Dahlan; Yunus Musa; Burhanuddin Rasyid; Muh. Farid Bdr (Hasanuddin University, 2013)
A series of researches was carried out to obtain mutant of maize induced by gamma rays irradiation. This initial report was from a study confirming the best dosage of irradiation at 50% lethal dosage (LD50) conducted at the Laboratory of Seed Science and Technology, Faculty of Agriculture, Hasanuddin University, Makassar from March to June 2012. The research was set up using split plot design of the Randomized Complete Block design. Data were analyzed using analysis of variance. Results showed that: Gamma ray dosage affected maize seed viability. The higher gamma ray dosage used resulted inmore inhibiton of maize seed germination. The best LD50 irradiation to induce putative mutation (M1) in maize seeds tested ranged from 100-200 Gy. The genotype Lamuru maize irradiated at 100 Gy were superior and were more viable with a percentage germination of 87.22% and vigor index of 4.48.